Use of perennial plants in the fight against gastrointestinal nematodes of sheep - Bosco, Antonio; Prigioniero, Antonello; Falzarano, Alessandra; Maurelli, Maria Paola; Rinaldi, Laura; Cringoli, Giuseppe; Quaranta, Giovanni; Claps, Salvatore; Sciarrillo, Rosaria; Guarino, Carmine; Scarano, Pierpaolo (Frontiers in Parasitology, 2023)
Background: Gastrointestinal nematodes (GINs) is a serious problem in ruminant pastures worldwide. They generate production losses, both from the point of view of the food chain and from the point of view of animal mortality. This study provides preliminary results concerning the use of pasture plants in Campania region (southern Italy) to control GINs in sheep. Methods: Sixteen species of wild and cultivated perennial plants present in the semi-natural pastures were sampled. All species were extracted with the conventional maceration technique, using three different solvents (H2O, EtOH and an EtOH:H2O (8:2) mixture) in order to extract different bioactive compounds. The total phenolic content (TPC, Folin-Ciocȃlteu assay) of all extract samples was preliminarily characterised. Each sample was aliquoted in six different concentrations and an in vitro egg hatching test (EHT) was conducted to evaluate the ovicidal effect on sheep GINs. Results: The results indicated that Cichorium intybus L. and Foeniculum vulgare Mill. extracts caused a high inhibition of egg hatching within 48 hours of exposure, showing efficacy (≥ 62.6%) at the first three higher concentrations than the others plant. Conclusion: The use of extracts of wild and cultivated perennial species in pastures can be a valid alternative to the use of anthelmintic synthetic drugs that in the long run generate problems such as anthelmintic resistance. Looking forward, further in vitro studies that also evaluate the in vitro effect of the extracts on ruminant cell cultures, and field application with in vivo studies, would likely lead to confirm the results obtained from preliminary in vitro EHTs. All aimed at evaluating the therapeutic potential and future applicability with specific plant cultures in pastures to achieve sustainable pest control.